Розвиток скотарства в аграрному господарстві німців і менонітів Таврійської губернії у другій половині ХІХ – на початку ХХ ст. - Замуруйцев, О.В. (Культура народов Причерноморья, 2013)
У статті розглядаються питання розвитку скотарства в німців і менонітів південного
регіону сучасної України, зокрема в Таврійській губернії, у другій половині ХІХ – на початку ХХ
століття. Автор, спираючись на конкретні статистичні дані, робить спробу визначити основні риси
та напрями, а також причини, що зумовили розвиток цієї галузі сільського господарства в
німецькомовних колоністів Півдня України. Актуальність обраної тематики пов’язана з важливою
роллю та економічним впливом німців і менонітів на загальний сільськогосподарський розвиток цих
територій у пореформену добу. статье рассматриваются вопросы развития скотоводства у немцев и меннонитов
южного региона современной Украины во второй половине XIX – в начале ХХ века (на примере
Таврической губернии). Автор, опираясь на конкретные статистические данные, делает попытку
определить основные черты и направления, а также причины, обусловившие высокое развитие этой
отрасли сельского хозяйства у немецкоязычных колонистов Юга Украины. Актуальность выбранной
тематики связана с важной ролью и экономическим влиянием немцев и меннонитов на общее
сельскохозяйственное развитие этих территорий в послереформенный период. Using Tavria Province of that time, the issues of the development of cattle breeding among the
Germans and the Mennonites of the southern region of modern Ukraine in the second half of the 19th – at the
beginning of the 20th centuries are being reviewed in the article. Basing himself on some concrete statistic data,
the author makes an attempt to fix principal features and tendencies as well as reasons which caused the
development of this agriculture branch among the German – speaking settlers of Southern Ukraine. The given
examples prove the fact that cattle breeding was gradually losing its role in comparison with agriculture at the
time. However, according to many important indices, cattle breeding was keeping its leading role, immediately
having an influence on the development of this agriculture branch in the region. In accrodance with the analysis
of archival documents, a conclusion has been made that the role of cattle breeding was henceforth coming, firstof all, to providing the inner needs of colonist farms with draught animals. At the same time, the problem of fine
– fleeced sheep breeding development, keeping its role in large colonist farms, has been studied. In the article
great importance is attached to the problem of providing German – speaking settlers of the South with various
kinds of domestic cattle in comparison with other groups of local population of this region. Great attention is
also paid to their achievements in breeding new species of domestic cattle which were very popular among the
local population. The chosen thematics urgency is connected with the important role and economic influence of
the Germans and Mennonites on the common agricultural development of these areas in the postreform epoch.